Global Research Trends on Environmental Sanitation and Pathogenic Bacteria: A Bibliometric Review - Zulfadilah Zulfadilah; Elsa Yuniarti (Jurnal Biologi Tropis, 2026)
Environmental sanitation plays a critical role in controlling pathogenic bacteria and protecting public health, yet research trends in this field require systematic evaluation. This bibliometric study examines global research developments, thematic structures, and scientific contributions related to environmental sanitation and pathogenic bacteria from 2015 to 2025. A total of 98 articles indexed in Scopus were systematically selected following PRISMA guidelines and analyzed using VOSviewer to assess publication trends, geographic and journal contributions, and keyword co-occurrence networks. Results indicate consistent growth in research output, reflecting sustained global interest in sanitation-related health issues. Leading contributions came from countries with strong research infrastructure and regions experiencing significant sanitation challenges. Keyword analysis identified core research themes including environmental sanitation, pathogenic bacteria, water quality, and public health, while emerging topics such as molecular detection methods and metagenomics represent evolving research directions. The findings demonstrate that research on environmental sanitation and pathogenic bacteria has developed into an increasingly interdisciplinary field. This study provides a comprehensive overview of current research landscapes and identifies knowledge gaps that may guide future investigations and evidence-based policy formulation to improve environmental sanitation systems and public health outcomes globally.